Understanding of Tourism Industries in ‎The Development of Halal Tourism in Aceh - Eddy Gunawan; Sartiyah Sartiyah; Nur Aidar (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2020)
The development of halal tourism requires readiness in various factors such as access, communication, environment, and services. The research was carried out in three district Aceh Province, namely in Banda Aceh City, Aceh Besar District, and Sabang City as tourism base areas. This research sample as many as 50 hotel business actors, 50 culinary delights, and 26 tourist objects, a total of 126 tourism business actors. Data analysis uses Binner Logit Regression, to determine the opportunities for tourism actors who are ready and not ready for halal tourism in the development of halal tourism in Aceh Province. The results showed that Accessibility, Communication, and Services had a positive effect on the development of halal tourism, while environmental factors do not affect the development of halal tourism in Aceh Province. Of all the factors, only services in tourism have high readiness and opportunities in influencing the development of halal tourism in Aceh Province.